-11x(x-5)=55-11x

Simple and best practice solution for -11x(x-5)=55-11x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11x(x-5)=55-11x equation:


Simplifying
-11x(x + -5) = 55 + -11x

Reorder the terms:
-11x(-5 + x) = 55 + -11x
(-5 * -11x + x * -11x) = 55 + -11x
(55x + -11x2) = 55 + -11x

Solving
55x + -11x2 = 55 + -11x

Solving for variable 'x'.

Reorder the terms:
-55 + 55x + 11x + -11x2 = 55 + -11x + -55 + 11x

Combine like terms: 55x + 11x = 66x
-55 + 66x + -11x2 = 55 + -11x + -55 + 11x

Reorder the terms:
-55 + 66x + -11x2 = 55 + -55 + -11x + 11x

Combine like terms: 55 + -55 = 0
-55 + 66x + -11x2 = 0 + -11x + 11x
-55 + 66x + -11x2 = -11x + 11x

Combine like terms: -11x + 11x = 0
-55 + 66x + -11x2 = 0

Factor out the Greatest Common Factor (GCF), '11'.
11(-5 + 6x + -1x2) = 0

Factor a trinomial.
11((-5 + x)(1 + -1x)) = 0

Ignore the factor 11.

Subproblem 1

Set the factor '(-5 + x)' equal to zero and attempt to solve: Simplifying -5 + x = 0 Solving -5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + x = 0 + 5 x = 0 + 5 Combine like terms: 0 + 5 = 5 x = 5 Simplifying x = 5

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {5, 1}

See similar equations:

| 15*28+34=x | | 2(b+5)=3b+8 | | 4+2(3u-7)=-2(7u-1)+6u | | 23x=3(8x+6) | | 6a-2B=20 | | -8n+20=124 | | 58-(55-2)=x | | 3x-25=2x+115 | | 72-18=x | | K^2-15k-54=0 | | 4n^2-10=0 | | 2(36-9)=x | | Ln-3x=-1 | | 4600/8000000 | | 75-18=x | | 4r+5=2r+11 | | 3a^2-9=11 | | 2x+10+x+(3x-16)=90 | | 4r-1=2 | | 4x-1/5x | | 2x+6+2x+(4x-8)=62 | | 13*(9-6)=n | | Y=4/9x-3 | | 5u-6+5(2u+3)=-3(u+1) | | 7(2x-3)=3(3x-11) | | 4xsquared=144 | | z-4+9=6 | | -1.476-1.6a=3.6a-0.28 | | z-4+ 9= 6 | | s^2+20s-17=0 | | u^2-28u=-15 | | 23.18+5.8= |

Equations solver categories